2020
DOI: 10.34257/gjmbravol20is17pg39
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Unethical Behavior Attitude of Tertiary Level Students of Bangladesh

Abstract: In this competitive world highly skilled manpower is considered to play key role in developing a nation. On the other hand, highly educated people are blamed for recent business and financial scandals. Moreover, studies established that pupils who deceive in their student life are found to be engaged in immoral workplace conduct. The Student today is the future leader of the country. Hence, the combination of quality with morality is emphasized in the universities of in many developed counties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Studies found a similar scenario, that is, the undergraduate students at a public and private university had partial understanding of IL skills and IE (Ferdows & Ahmed, 2015; Islam & Tsuji, 2010; Shoeb, 2011). In a very recent study (Arefeen et al, 2020) on the unethical behaviour attitude of tertiary level students in Bangladesh, researchers found very low‐level awareness of ethics in their study process. The authors assumed the absence of ethical contents on the curriculum is responsible for this.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies found a similar scenario, that is, the undergraduate students at a public and private university had partial understanding of IL skills and IE (Ferdows & Ahmed, 2015; Islam & Tsuji, 2010; Shoeb, 2011). In a very recent study (Arefeen et al, 2020) on the unethical behaviour attitude of tertiary level students in Bangladesh, researchers found very low‐level awareness of ethics in their study process. The authors assumed the absence of ethical contents on the curriculum is responsible for this.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers suggested that the use of plagiarism checkers has failed to stop the practice just as academic codes of conduct by the postgraduate researchers and lecturers have not worked (Amunga, 2013). It was strongly recommended that university administration should introduce ethics courses as university prerequisite courses apart from the compulsory core courses (Arefeen et al, 2020; Brown, 1999; Carbo, 2005; Carbo & Almagno, 2001; Dadzie, 2011; Maughan, 2001; Naveed & Mahmood, 2021; Nero, 1999). So, behaviour change should be brought about by a deep understanding of IL and IE and the need to embrace positive practices in regard to access and use of information in university and life‐long practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lack of these components led to the massive accounting crises and frauds in the international corporate sectors. Financial firms, publicly traded companies, and private enterprises have either being declared distressed or have totally closed down as a result of cases of fraud, fabrication, and purposeful exaggerations of companies' accounts as well as other professional misconduct (Arefeen, Mohyuddin, & Khan, 2020;Bakre, 2007;Uddin, Khan, & Mohammad, 2015). The credibility of financial statements and transparency has been destroyed by the demise of large corporations like Enron, WorldCom, Global Crossing, and Parmalat in the United States and Parmalat in Italy.…”
Section: Assessment Of Need Of Ethics In Accounting Educationmentioning
confidence: 99%
“…Moreover, students in higher education will become the country's future leaders (Yang, 2023a). Higher education cultivates students in all fields of society, such as doctors, engineers, scholars, and intellectuals, to contribute to society and realize the country's overall development, personnel management, and progress (Arefeen et al, 2020). Therefore, higher education plays a significant role in developing the country and cultivating talent (Shen & Hu, 2021).…”
Section: Introductionmentioning
confidence: 99%